2021
DOI: 10.1111/1755-0998.13338
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐level assembly of southern catfish (silurus meridionalis) provides insights into visual adaptation to nocturnal and benthic lifestyles

Abstract: The Southern catfish (Silurus meridionalis) is a nocturnal and benthic freshwater fish endemic to the Yangtze River and its tributaries. In this study, we constructed a chromosome-level draft genome of S. meridionalis using 69.7-Gb Nanopore long reads and 49.5-Gb Illumina short reads. The genome assembly was 741.2 Mb in size with a contig N50 of 13.19 Mb. An additional 116.4 Gb of Bionano and 77.4 Gb of Hi-C data were applied to assemble contigs into scaffolds and further into 29 chromosomes, resulting in a 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 148 publications
(151 reference statements)
5
36
0
Order By: Relevance
“…Nevertheless, the heterozygosity estimated for TARdn1 is one of the highest reported for a fish species. To our knowledge, this is the highest heterozygosity estimated for a fish through k -mer analysis, with other reported values ranging from 0.1% (Tibetan loach Triplophysa tibetana and Murray cod Maccullochella peelii ) to 0.9% (Java medaka Oryzias javanicus ) (Austin et al, 2017; Ge et al, 2019; Gong et al, 2018; Lu et al, 2020; Nguinkal et al, 2019; Takehana et al, 2020; Vij et al, 2016; Yang et al, 2019; H. H. Zhang et al, 2020; Zheng et al, 2021). Even the heterozygosity estimated through SNPs (0.64%) is high compared to estimations from other fish using the same method (e.g.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, the heterozygosity estimated for TARdn1 is one of the highest reported for a fish species. To our knowledge, this is the highest heterozygosity estimated for a fish through k -mer analysis, with other reported values ranging from 0.1% (Tibetan loach Triplophysa tibetana and Murray cod Maccullochella peelii ) to 0.9% (Java medaka Oryzias javanicus ) (Austin et al, 2017; Ge et al, 2019; Gong et al, 2018; Lu et al, 2020; Nguinkal et al, 2019; Takehana et al, 2020; Vij et al, 2016; Yang et al, 2019; H. H. Zhang et al, 2020; Zheng et al, 2021). Even the heterozygosity estimated through SNPs (0.64%) is high compared to estimations from other fish using the same method (e.g.…”
Section: Resultsmentioning
confidence: 64%
“…Triplophysa tibetana and Murray cod Maccullochella peelii) to 0.9% (Java medaka Oryzias javanicus) (Austin et al, 2017;Ge et al, 2019;Gong et al, 2018;Lu et al, 2020;Nguinkal et al, 2019;Takehana et al, 2020;Vij et al, 2016;Yang et al, 2019;Zheng et al, 2021). Even the heterozygosity estimated through SNPs (0.64%) is high compared to estimations from other fish using the same method (e.g.…”
Section: Estimation Of Heterozygositymentioning
confidence: 90%
“…Our previous study identified sex-linked DNA markers and demonstrated an XX/XY sex-determination system in this species [12]. We also generated a whole-genome assembly anchored on chromosomes for an XX female individual [13]. Yet, little is known about genetic sex determination in southern catfish beyond males being the heterogametic sex, and its sex locus and SD gene remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Through combining the third-generation sequencing method (Oxford Nanopore or PacBio) and the high-through chromosome conformation capture (Hi-C) technology, genomes can be assembled into the chromosome level, which have been successfully used in many fish species. 29–31 Chromosome-level genomes have also been reported in catfishes, such as channel catfish ( Ictalurus punctatus ), 32 yellow catfish ( Pelteobagrus fulvidraco ), 33 giant devil catfish ( Bagarius yarrelli ), 34 Southern catfish ( Silurus meridionalis ), 35 Chinese longsnout catfish ( Leiocassis longirostris ), 36 striped catfish ( Pangasianodon hypophthalmus ), 37 and redtail catfish ( Hemibagrus wyckioides ). 38 These chromosome-level assemblies have been widely used as reliable reference genomes for studies of many fields, including ecological adaptation, 35 , 39 , 40 genome evolution, 41–43 gene evolution, 44 , 45 immunology, 46–48 and identification of target-trait-related genes, 49 , 50 in aquatic animals.…”
Section: Introductionmentioning
confidence: 99%